Estudio de factibilidad para crear una empresa comercializadora de biofermentos, para la alimentación de cerdos en el municipio de Pereira, Risaralda (2013)
The importance of excreta management at porcine level has been generalized especially by the great environmental impact at the regional level, where its inappropriate dumping contaminates river basins and impairs soil productivity, which has become in an environmental management problem. Contamination and damage to the environment where pig excreta are spread can be solved through a fermentation process carried out with a biofermenter called Biolac, developed at the University of Applied and Environmental Sciences of Bogota Colombia, by Dr. RAFAEL EDUARDO MENDOZA CASTRO, which uses the porcine, to generate from the swine excreta a food with a high nutritional protein content for them (pigs), helping to reduce food costs in comparison with the commercial concentrate and fundamentally helps to mitigate the environmental damage. Biolac is a product obtained through Biofermentation with stimulators of bacterial growth applied to porcine excreta, resulting in a food with high protein content whose main destination is for consumption (food) especially the porcine sector.